2002
DOI: 10.1159/000065628
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Damage Induced by Subchronic Administration of Preferential Cyclooxygenase-1 and Cyclooxygenase-2 Inhibitors in Rats

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are well known to induce gastrointestinal damage including bleeding, ulceration and perforation in humans and animals. The aim of this study was to compare the effects of two oxicams, preferential cyclooxygenase (COX)-1 or COX-2 inhibitors, on both gastric mucosa and some biological parameters (hematological, hepatic and renal) after subchronic administration (14 and 28 days) in rats. Neutrophil infiltration was also assessed. Equipotent doses of meloxicam (3.75 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Não houve alterações significativas das plaquetas (Tabelas 1 e 3). Este fato também foi observado em ratos Wistar tratados com meloxicam (3,75 mg/kg, a cada 24 horas, por via intragástrica durante 14 e 28 dias) 10 . Por outro lado, podem ocorrer trombocitopenia com o uso de AINES 1 , contrariando os dados obtidos neste trabalho.…”
Section: Resultsunclassified
“…Não houve alterações significativas das plaquetas (Tabelas 1 e 3). Este fato também foi observado em ratos Wistar tratados com meloxicam (3,75 mg/kg, a cada 24 horas, por via intragástrica durante 14 e 28 dias) 10 . Por outro lado, podem ocorrer trombocitopenia com o uso de AINES 1 , contrariando os dados obtidos neste trabalho.…”
Section: Resultsunclassified
“…Though, there is limited information about GI toxicity of meloxicam in experimental animals (Villegas et al, 2002;Gambero et al, 2005), it has been shown to possess varying degree of GI toxicity in clinical cases (Layton et al, 2003;MacDonald et al, 2003;Laporte et al, 2004;Richy et al, 2004).There is no direct evidence from the present study that aminoguanidine has reduced GI toxicity of meloxicam, but aminoguanidine has been found to be gastroprotective in adjuvant-induced arthritic rats exposed to indomethacin (Kato et al, 1999) and acetic acid-induced ulcers (Akiba et al, 1998). In conclusion, the use of aminoguanidine will help in reducing the dose of meloxicam, showing synergistic antinociceptive effect and might reduce GI toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these findings, meloxicam and ketoprofen did not alter the hematological parameters of healthy ponies (Pozzobon et al, 2009). Villegas et al (2002) reported that piroxicam and meloxicam did not significantly affect hematological parameters in rats. Some enzymes, proteins, and nucleic acids in the blood associated with specific tissue damage can be used to detect most drug-related adverse effects and, in some cases, to determine the prognosis (Tang and Lu, 2010;Özdemir and Traş, 2018).…”
Section: Discussionmentioning
confidence: 98%